2021
DOI: 10.1111/ijfs.15039
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and profiles of fatty acids, vitamin E and carotenoids during flax (Linum usitatissimum L.) seed capsule maturation

Abstract: This study investigated the profiles of major fatty acids, vitamin E and carotenoids at metabolic and transcription levels in fibre flaxseed capsule at six mature stages. From 5 days after flowering (DAF) to 15 DAF, the percentages of a-linolenic acid and oleic acid notably increased, whereas palmitic acid and linoleic acid dramatically decreased, and finally remained stable till S6. The content of c-tocopherol was progressively raised to the maximum at the last stage, while a-tocopherol presented a gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…You et al suggested that FAD2a-1/FAD2a-2, FAD2b-1/FAD2b-2, and FAD3a/FAD3b play a crucial role in the synthesis of linseed oil FAs [46]. The same role of these genes was also demonstrated in other studies [44,[48][49][50].…”
Section: Introductionmentioning
confidence: 59%
“…You et al suggested that FAD2a-1/FAD2a-2, FAD2b-1/FAD2b-2, and FAD3a/FAD3b play a crucial role in the synthesis of linseed oil FAs [46]. The same role of these genes was also demonstrated in other studies [44,[48][49][50].…”
Section: Introductionmentioning
confidence: 59%
“…However, exogenous ALA can reduce the accumulation of ROS and maintain the stability of the chloroplast membrane under stress environments. In addition, ALA inhibits chlorophyll synthesis by reducing the level of Mg-chelatase and Protochlorophyllide oxidoreductase 41 . The higher concentration (5–40 mM) of ALA led to the accumulation of several chlorophyll intermediaries in plants, such as protochlorophyllide, protoporphyrin IX, and protoporphyrin magnesium 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that water stress reduces the amount of carotenoids in plants 44 . ALA application enhances carotenoid biosynthesis by positively regulating enzymes such as geranylgeranyl diphosphate synthase, phytoene synthase, phytoene desaturase, and lycopene β-cyclase 41 . In addition, ALA application has been found to increase the content of carotenoids, as well as improve chlorophyll a, chlorophyll b, and total chlorophyll, as demonstrated in another study 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation